2001
DOI: 10.1006/viro.2000.0820
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human bcl-2 and bcl-X Genes on Dengue Virus-Induced Apoptosis in Cultured Cells

Abstract: Infection of dengue viruses (DENs) can cause human dengue fever, hemorrhagic fever, or shock syndrome. Although DEN-induced apoptosis has been implicated in pathogenesis of the DEN-related diseases, the underlying mechanism remains largely unexplored. In this study, we investigated the effect of ectopic expression of human bcl-2 and bcl-X genes on DEN-induced apoptosis in cultured cells. We employed a human isolate of DEN serotype 2 (DEN-2), PL046, which not only caused cell-cycle arrest in the G1 phase but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…To investigate the role of MAVS in viral infection, we determined the protein expression pattern of MAVS in mock-and DEN-2-infected N18 cells, a mouse neuroblastoma cell line that is susceptible to DEN-2 infection and has been used for studies of DEN-2 (35,45). In addition to the band for full-length MAVS, another major protein band of smaller molecular size was noted, and its abundance increased further during DEN-2 infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of MAVS in viral infection, we determined the protein expression pattern of MAVS in mock-and DEN-2-infected N18 cells, a mouse neuroblastoma cell line that is susceptible to DEN-2 infection and has been used for studies of DEN-2 (35,45). In addition to the band for full-length MAVS, another major protein band of smaller molecular size was noted, and its abundance increased further during DEN-2 infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the cleavage of isotope-labeled MAVS, Flag-tagged MAVS and its mutants were transcribed and translated in vitro by using TNT rabbit reticulocyte lysate (Promega) supplemented with [ 35 S]methionine (PerkinElmer), and the Flag-tagged proteins were purified by binding to Flag-Sepharose beads (Sigma-Aldrich). Ten microliters of 35 S-labeled Flag-tagged protein-binding beads was incubated with 1 U of recombinant active caspase-3 in reaction buffer as described above. After 1 h of incubation at 37°C, the reaction products were eluted in sample buffer, resolved by SDS-PAGE, and analyzed by autoradiography.…”
mentioning
confidence: 99%
“…Rather than autoantibody-induced cell death, several studies have focused on the apoptosis that is directly induced by DENV infections (52)(53)(54). Studies have demonstrated that DENV infections elicit proapoptotic responses involving the suppression of Bcl-2 and Bcl-x L as well as the induction of Bax (40)(41)(42). The induction of TRAIL has been reported in human endothelial-like ECV304 cells following DENV infection (55).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Bcl-2 family members, Bax and Bcl-x L , which previous studies have shown to be involved in the DENV-mediated regulation of cell death (40)(41)(42)(43), were analyzed for comparison. RT-PCR analysis revealed that the mRNA expression levels of the proapoptotic TRAIL-R1 (DR4) and Bax were upregulated after subcytotoxic DENV challenge (Supplemental Fig.…”
Section: Denv-challenged Endothelial Cells Are Highly Sensitive To Anmentioning
confidence: 99%
“…Once internalized, the apoptotic induction elicited by dengue virus has been well-characterized. [25][26][27] It would be interesting to determine if antibody-mediated GRP78 ligation mimics viral binding and infection. Thereby, GRP78 would still provide a protective function, but in this case the protective function would be to the surrounding cells and the organism as a whole.…”
mentioning
confidence: 99%